ASSOCIATION OF HISTOPATHOLOGICAL CHARACTERISTICS AND TERT (TELOMERASE REVERSE TRANSCRIPTASE) IMMUNOEXPRESSION WITH METASTATIC RATE IN CUTANEOUS MALIGNANT MELANOMA - Riesye Arisanty 1, Bayu Perkasa Rosari 2*, Puspita Eka Wuyung 3, Maria Angela Putri Maharani 4 (Chelonian Research Foundation, 2024)
Cutaneous malignant melanoma (MM) is a malignant tumor with a high mortality rate. Histopathological characteristics are prognostic predictive factors of cutaneous MM, in which tumor thickness >2 mm and mitotic rate ≥5/mm2 correlate with a worse survival rate. A mutation in MM can occur at telomerase reverse transcriptase (TERT) promoter region, which leads to unlimited cell proliferation. Telomerase also increases metastatic risk. This study aims to determine the association between histopathological characteristics and TERT immunoexpression with metastasis in cutaneous MM. The study samples are 30 metastatic and 30 non-metastatic cutaneous MM in the Anatomical Pathology Department FKUI/RSCM, from January 2011 to July 2023. Histopathological characteristics (tumor thickness, mitotic index, lymphovascular invasion, and perineural invasion) were assessed, and anti-TERT antibodies were used for immunohistochemistry staining. Histopathological characteristics and TERT immunoexpression data were analyzed to determine their association with metastasis. Histopathological features that correlate significantly with metastasis are tumor thickness >2 mm (p=0.006) and mitotic index ≥5 mitosis/mm2 (p=0.008). Multivariate analysis showed a significant association between high TERT immunoexpression and metastasis in cutaneous MM (p<0.001, aOR=56.1). This study concludes that high TERT immunoexpression increases the metastatic rate in cutaneous MM. Greater tumor thickness and a higher mitotic index are associated with metastasis in cutaneous MM. Keywords: Cutaneous Malignant Melanoma; Immunohistochemistry; Metastasis; TERT